Great ideas in teaching health - Champeau, Donna (Allyn and Bacon, 1998)
All too often teachers are challenged with the task of making their lessons inviting, intriguing, and most of all, fun for their students. The ideas and activities in this book are favorites that have been tried and tested in the classroom and submitted by health educators from across the United States. This compilation of some of the best ideas for the college-age student covers a wide range of health-related areas. Each teaching idea provides readers with a strategy to help teach new health concepts as well as reinforce previously learned material. One of the book's strengths is its versatility, with 43 generic activities that can be applied and adapted to be used with any other health book.KEY MARKET A great resource for all health instructors at all levels.